DRAMA AND ROLE-PLAY AS EFFECTIVE METHODS FOR TEACHING ENGLISH TO 8TH GRADE STUDENTS (SCIENCE TIME JOURNAL, 2026)
This article explores the effectiveness of drama and role-play methods in teaching English to 8th grade students. In modern education, the development of communicative competence is a key objective, while traditional grammar-translation methods no longer fully meet learners’ communicative needs. Therefore, interactive approaches such as drama and role-play have gained increasing importance, as they create realistic communication situations and encourage active student participation. The study analyzes the role of these methods in expanding vocabulary, improving pronunciation, developing fluency, and enhancing listening comprehension skills. Additionally, their positive impact on reducing speaking anxiety and fostering social interaction skills is highlighted. The findings demonstrate that integrating drama and role-play into classroom practice significantly increases students’ motivation and communicative activity, making them effective tools for creating a dynamic and learner-centered learning environment.